Hierarchical Formation of Fibrillar and Lamellar Self-Assemblies from Guanosine-Based Motifs. (28th June 2010) - Neviani, Paolo; Sarazin, Dominique; Schmutz, Marc; Blanck, Christian; Giuseppone, Nicolas; Spada, Gian Piero
Abstract : Here we investigate the supramolecular polymerizations of two lipophilic guanosine derivatives in chloroform by light scattering technique and TEM experiments. The obtained data reveal the presence of several levels of organization due to the hierarchical self-assembly of the guanosine units in ribbons that in turn aggregate in fibrillar or lamellar soft structures. The elucidation of these structures furnishes an explanation to the physical behaviour of guanosine units which display organogelator properties.